Risks and Benefits of Breastfeeding in COVID-19: Integrative Literature Review - Carvalho, Ana Clara Alves de; Reis, Gabriel Campos Carvalhaes; Oliveira, João Guilherme de Moura; Borges, Raquel Ferreira (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective The present article seeks to consolidate existing knowledge on breastfeeding during the SARS-CoV-2 pandemic.Data source Articles from 2020 and 2021 collected from the PubMed, CAPES, Virtual Health Library, Google Scholar, SciELO, and UpToDate databases were analyzed. Books and government documents published in the last decade (2010–2020) were also consulted.Study Selection Sixteen works were used in the present study. The date of publication and discussion of SARS-CoV-2 transmission through breast milk were the inclusion criteria. Thus, articles containing repeated information or with no relevance to add to the production were excluded. Data collection comprised critical reading and synthesis of the main information obtained on the subject, which were performed for the preparation of the present study. The research took place in the period from March 27 to April 2, 2021.Synthesis of the data Breast milk has diverse benefits for both the nursing mother and the infant. The presence of viral RNA by real-time polymerase chain reaction (RT-PCR) in milk from disease-positive mothers has been detected in a few cases, and infant infections in these conditions suggest oral transmission of maternal or third-party origin. The virulence of the novel coronavirus in human milk is not confirmed, while significant amounts of exclusive antibodies are.Conclusion Lactation in the context of COVID-19 has shown greater benefits than risks of vertical transmission. Therefore, it should be encouraged when possible.
Keywords: COVID-19; SARS-CoV-2 infection; breastfeeding; vertical infectious disease transmission; immunology